Small millets research: achievements during 1947-97 - SEETHARAM, A (The Indian Journal of Agricultural Sciences, 2013)
In India 6 small millets, viz finger millet [Eleusine coracana (L.) Gaertn.], foxtail millet [Setaria italica (L.)Beauv.], kodo millet (Paspalum scrobiculatum L.), little millet (Panicum sumatrense Roth ex Roem. & Schult.), prosomillet (Panicum miliaceum L.) and barnyard millet [Echinochloa frumentacea (Roxb.) Link], are cultivated as grain and feed crops. Though during the last 50 years the area under small mi millet decreased by 4 million ha. there was no reduction in their overall production. The finger millet, a major contributor to the sustenance of production level, accounts for about 50% area and 65% production under small millets. The productivity of small millets other than finger millet remained stagnant around 450 kg/ha in the last 5 decades. The small millets have been the least priority crops in respect of their promotion and development. In this article an attempt was made to review the progress of research in these millets during the last 5 decades.